"Customer Protection Against the Circulation of Counterfeit Money in Au-tomated Teller Machines from the Perspective of Sadd adz-Dzari'ah" - Budiman, Mutya Fradilla; Hidayat, Rahmat (LEGAL BRIEF, 2025)
The circulation of counterfeit money obtained by customers through Automated Teller Machines (ATMs) is highly detrimental to customers and poses a real threat to the security of banking transactions. This study aims to examine customer protection and accountability regarding the circulation of counterfeit money that comes out of ATMs, also from the perspective of sadd adz-dzari'ah. This research employs a normative legal research method, which focuses on the study of applicable legal norms or rules. In this study, three approaches are used: case approach, legislative approach, and conceptual approach. Sadd adz-dzari'ah is a concept in Islamic law that prevents anything that may cause harm or danger. The results of this analysis indicate that banks have full control over the operations of ATMs. Thus, banks are required to provide forms of protection and accountability to customers who receive counterfeit money through ATMs. Customer protection is preventive, involving initial protection efforts such as regular checks, internal monitoring, and education for customers. The bank's accountability is reactive, carried out after an incident of loss occurs for customers due to negligence or mistakes by the bank, such as internal investigations, compensating for losses if it is proven that the money dispensed from the ATM was counterfeit, or enhancing security systems to prevent similar incidents from occurring. Based on the principle of sadd al-dzari’ah, the protection of customers from counterfeit money emphasizes preventive measures against all forms of harm that may arise, both individually and systematically. This research concludes that the protection of customers against the risk of counterfeit money from ATMs must be a serious concern through relevant government actions to establish clear, firm regulations that consumer interests